Neznámá epizoda ze života Bolka IV. Opolského. K interpretaci listiny Alberta ze Šternberka z roku 1392 - Radek, David (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The present study deals with the youth of Bolko IV of Opole who has not yet received much attention in historiography. Using a hitherto unknown source, the author points to the small role played by the Opole prince in Sigismund of Luxembourg‘s war against the Turks in 1392.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne